MENINGKATKAN KETERAMPILAN MEMBUAT PEYEK RINUAK MELALUI METODE DEMONSTRASI PADA ANAK TUNAGRAHITA RINGAN - Endang Purwati (Universitas Negeri Padang, 2015)
Abstract. The purpose of this research are: 1) to describe the process of learning to make a peyek rinuak improve skills through demonstration method and 2) Prove demonstration method can improve the skills to make peyek rinuak for mild mental retardation children in State SDLB D.VI class 64 Surabayo Lubuk Basung. This type of research is action, action taken in the form of collaboration with colleagues. Subjects three children mild mental retardation D.VI class and one teacher. The data obtained through observation, testing. Then analyzed qualitatively and quantitatively. The results showed that 1) the learning process makes peyek rinuak using the demonstration conducted by two cycles. I cycle with seven meetings and the second cycle of four meetings. Each cycle begins with the planning, implementation (initial activities, core and end), observation, and analysis and reflection. 2) The results of the study by using the method in making a peyek rinuak demonstrations increased. It can be seen from the data before action children's ability to perform 20 steps to make peyek rinuak namely: HD (30%), RK is (40%) and YN 60%. While at the end of the first cycle of HD capability increased to (77.5%) and RK (77.5%) and YN (87.5%). After the second cycle increased to HD capability (95%) and RK (97.5%) and YN be (100%). It can be concluded that both of these third increased ability to make peyek rinuak after being given intensive demonstration method to mild mental retardation children in the class D.VI in State SDLB 64 Surabayo Lubuk basung. Recommended to teachers in order to use the method of demonstration in teaching other skills. Kata kunci: Peyek Rinuak; Metode Demonstrasi; Anak Tunagrahita Ringan